Progress in Understanding the Relationship between Diabetes and Host Intestinal Microbiota and Diet-Mediated Microbiota Regulation - WANG Danping, XU Jinzhao, ZHANG Xiaohang, NING Ke, LIU Ye, XU Yuanzhi, XIE Qinggang, XU Xiaoxi (Shipin Kexue, 2023)
Diabetes is a metabolic disease characterized by insulin secretion disorder. When serious, it can cause various complications (cardiovascular and cerebrovascular diseases, cataract and other eye diseases, kidney disease and cancer), bringing a huge economic burden to the society and families and torturing patients. The risk of diabetes is not only related to genes, living pressure and working environment, but also directly related to patients’ lifestyles and dietary habits. An unhealthy diet (high in fat and sugar) can induce the intestinal flora to produce adverse metabolites, which can in turn promote the occurrence and development of diabetes. Intestinal flora imbalance is widespread in the pathogenesis of various types of diabetes. As an important factor influencing the intestinal flora, diet is not only essential to maintain body functions, but also can contribute to intestinal immunity. Regulation of the intestinal environment through diet is expected to be an effective preventive means and auxiliary therapy for diabetes. By synthesizing the existing literature, this article discusses the features of the intestinal flora and the mechanism of the effect of diet-mediated regulation of the intestinal flora on diabetes based on systematic medical theory, and reviews the role scientific diet plays in regulating intestinal homeostasis and immunity and consequently reducing the incidence and complications of diabetes. We hope that this review will provide a basis for early diagnosis and prevention and adjuvant treatment of diabetes.